PERAMALAN JUMLAH TAMU DAN PENGUNJUNG DINNER HOTEL MEGA BINTANG SWEET KABUPATEN BLORA DENGAN PENDEKATAN ARIMA - Irfana Maulana Ismail; Wellie Sulistijanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Mega Bintang Sweet Hotel is one of the hotels in Blora Regency. Article is forecasting comparative analysis of number of guess room occupancy at Mega Bintang Sweet Hotel, Blora, Central Java using forecasting methods: Autoregressive Integrated Moving Average (ARIMA). Article used 60 data from January 2012 to December 2016, and the results of research using forecasting method suggest that the right model is ARIMA (0,1,1) model with the following equation : Zt = -0,6840Zt-1 – 0,4813t-2 + at + 1,0135at-1 and the smallest MSE is 7754.  Keywords : forecasting, guess room occupancy, MSE.